2020
DOI: 10.1177/2324709620924203
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Fulminant Hepatitis Secondary to Cocaine in the Setting of β-Blocker Use

Abstract: Background. Fulminant hepatitis is acute hepatic injury with severe decline in hepatic function manifested by encephalopathy, hypercoagulable state, jaundice, renal failure, hypoglycemia, or a constellation of these symptoms in patients without preexisting liver disease. Etiologies include viral infections, hepatotoxic drugs, autoimmune diseases, vaso-occlusive diseases, sepsis, and malignant infiltration. Case Report. A 56-year-old man presented with acute heart failure in the setting of cocaine use. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has been suggested that cocaine reduces hepatic blood flow, causing shock liver, or ischemic hepatitis [ 10 , 11 ]. The findings of shock liver have been associated with cocaine-induced hepatitis in several case reports [ 9 , 11 - 13 ]. Cocaine-induced ischemic hepatitis is consistent with the features in our case, as the patient’s condition progressed to hypotension and tachycardia, requiring vasopressors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that cocaine reduces hepatic blood flow, causing shock liver, or ischemic hepatitis [ 10 , 11 ]. The findings of shock liver have been associated with cocaine-induced hepatitis in several case reports [ 9 , 11 - 13 ]. Cocaine-induced ischemic hepatitis is consistent with the features in our case, as the patient’s condition progressed to hypotension and tachycardia, requiring vasopressors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite the global COVID-19 pandemic, European authorities have intercepted at seaports growing amounts of cocaine in 2020 [5]. All the while, case reports detailing the harmful consequences of cocaine use abound [7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%